4(x-1)+3(x+1)=

Simple and best practice solution for 4(x-1)+3(x+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-1)+3(x+1)= equation:


Simplifying
4(x + -1) + 3(x + 1) = 0

Reorder the terms:
4(-1 + x) + 3(x + 1) = 0
(-1 * 4 + x * 4) + 3(x + 1) = 0
(-4 + 4x) + 3(x + 1) = 0

Reorder the terms:
-4 + 4x + 3(1 + x) = 0
-4 + 4x + (1 * 3 + x * 3) = 0
-4 + 4x + (3 + 3x) = 0

Reorder the terms:
-4 + 3 + 4x + 3x = 0

Combine like terms: -4 + 3 = -1
-1 + 4x + 3x = 0

Combine like terms: 4x + 3x = 7x
-1 + 7x = 0

Solving
-1 + 7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 7x = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 7x = 0 + 1
7x = 0 + 1

Combine like terms: 0 + 1 = 1
7x = 1

Divide each side by '7'.
x = 0.1428571429

Simplifying
x = 0.1428571429

See similar equations:

| 217.25=3 | | 4x-(2x+5)=3x-10 | | 6m-6=6m+18 | | 2x+3x+3=-12 | | 21p-62=38+p | | 8x+12-2x-5=3 | | y=kx+f | | 2(2+5x)=9(x-1) | | 81c^2+18c+1= | | 9[5-7(x-1)]+6[(5x+7)-8]=11x-336 | | (1-5j)+(-2-6j)=-1-11j | | 6x+x^2=84 | | 9c^2-8c-1= | | 4-x=4x+19 | | -3(x+3)=5x | | 0.004(2-k)+0.09(k-7)=1 | | 1x+4x=43 | | 13-4x+12=13 | | 4t-3=37-t | | 5b-7=-13 | | 5x+22+2x=-48 | | x-7/6=1-x/7 | | 5g+7+3g=31 | | 60a^5-24a^4+36a^3= | | 15z+30=15y+30 | | 6(W+3)=-2(5W-5)+2W | | 3(9+1)-5=(2y-2) | | k-7=10k-16 | | x^3-4x^2+x-9=0 | | 3i+10=14i-12 | | n^2-81= | | 8y+20=16-12 |

Equations solver categories